An Effect Realization on Temporality, Aspectuality, and Capital in English Indonesian Language - Yossy Fadly (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In typological linguistics, the terms “kala,” “aspect,” “mode/modality” are used and are known as verb paradigms or verbal systems (morphosyntactically) and verb semantic aspects (semantically) in describing language characteristics. However, these terms are treated as parallel, even though all three leave theoretical problems. Kala and aspect are grammatical categories, while modality is semantic notation. In addition, there is also the term mode which is often assumed to be a synonym for modality even though the two are related different concepts. Therefore, this study attempts to answer these theoretical problems by referring to temporality, aspectuality, and modality and describing their realization in English and Indonesian to gain a comprehensive understanding. This research is a contrastive analysis that compares English and Indonesian. Data were collected from two synchronic corpora, namely the Corpus of Contemporary American English (COCA) for English data and Wortschatz Leipzig Corpora Collection for Indonesian data. The analysis results show that English and Indonesian have different realizations of these notes; English is more varied in realizing temporality, while Indonesian is more varied in learning aspectual. The manifestations of English modalities are more diverse, which include core and quasi-modal. Based on this analysis, it can be concluded that English is more affluent in morphosyntax and syntax, while Indonesian is richer in morphology.